Foam paper laminate
A foamed paper laminate with a biomass-derived urethane resin in the printed layer addresses heat resistance and environmental concerns, ensuring effective use in foamed paper containers.
Patent Information
- Application Number
- JP2020123027
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-17
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2040-07-17
AI Technical Summary
Foamed paper containers require a printed layer that exhibits excellent heat resistance, foaming followability, and ethanol resistance, yet existing biomass resins fail to meet these requirements due to insufficient heat resistance during the heat processing step, leading to peeling issues and environmental concerns.
A foamed paper laminate comprising a base paper with a thermoplastic resin layer and a printed layer containing a binder resin made from a biomass-derived urethane resin, specifically with structural units derived from castor oil polyol and optionally polyester polyol, to enhance heat resistance, foaming followability, and ethanol resistance.
The laminate achieves excellent heat resistance, foamed appearance, and ethanol resistance, making it suitable for use in foamed paper containers while reducing environmental impact by utilizing biomass resins.
Smart Images

Figure 0007610367000005 
Figure 0007610367000006 
Figure 0007610367000001
Abstract
Description
[Technical field]
[0001] SUMMARY OF THE DISCLOSURE An embodiment of the present invention relates to a foam paper laminate. [Background technology]
[0002] Since foam containers have excellent heat insulation properties, they are widely used as containers for storing foods containing hot or cold liquids. In particular, foam containers are indispensable for products generally called "cup noodles," which are instant noodles such as ramen, udon, and soba noodles stored in a container and can be eaten a few minutes later by simply pouring an appropriate amount of hot water over them. As foam containers for cup noodles, polystyrene foam containers and foam paper containers are known, but in recent years, foam paper containers have been attracting attention from the viewpoints of environmental load and safety.
[0003] A foamed paper container is manufactured using a foamed paper material having a paper base material and a thermoplastic resin layer that foams by heating during container manufacturing and forms a heat insulating layer. Usually, a printed layer including a printed pattern such as a decorative pattern, a company name, or a barcode is formed on the surface of a foamed paper container (foamed paper material). Therefore, it is desirable that the printed layer has excellent foaming followability without hindering foaming when the thermoplastic resin layer of the foamed paper material foams by heating to form a heat insulating layer. In addition, it is desirable that the surface (printed surface) of the printed layer in the foamed paper laminate after the thermoplastic resin layer is foamed is smooth, free of cracks and blisters, and has an excellent appearance (hereinafter referred to as "foamed appearance"). In addition, it is desirable that the printed surface has excellent various resistances such as abrasion resistance and heat resistance required during container manufacturing. Furthermore, since solvents such as ethanol are widely used for disinfection in the food industry, the printed layer is also required to have solvent resistance such as ethanol resistance.
[0004] Conventionally, gravure ink or flexographic ink has been used to form a printing layer of a foamed paper container. For example, Patent Document 1 and Patent Document 2 disclose an ink for a foamed paper container (foam cup) that contains a binder resin and a pigment as an ink for forming a printing layer of the foamed paper container, and the binder resin contains a urethane resin.
[0005] On the other hand, in order to build a recycling-oriented society, biomass resins have been attracting attention in recent years. For example, polylactic acid (PLA) or polyethylene resins derived from biomass raw materials have been commercialized as film-shaped biomass resins. In addition, Patent Documents 3 to 5 disclose environmentally friendly inks using biomass resins and laminates using the inks. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2009 / 119800 [Patent Document 2] JP 2018-109131 A [Patent Document 3] JP 2018-058955 A [Patent Document 4] JP 2014-004799 A [Patent Document 5] JP 2014-005414 A Summary of the Invention [Problem to be solved by the invention]
[0007] From the viewpoint of constructing a recycling-oriented society as described above, it is desirable to adopt biomass resins using raw materials derived from animals and plants in the field of foamed paper containers instead of conventional resins obtained from fossil fuels. On the other hand, the printed layer in the foamed paper container is required to have special properties such as heat resistance, foaming followability, and foaming appearance in addition to various properties such as abrasion resistance and ethanol resistance. In particular, the heat resistance of the printed layer during heat processing is important.
[0008] In the use of foamed paper containers, the substrate expands during the process of forming the foamed layer during the manufacture of the container due to the heating process. Therefore, if the heat resistance of the printed layer is insufficient, problems such as the printed layer peeling off from the substrate during the container manufacturing process and accumulating on the equipment are likely to occur. Therefore, the printed layer in the foamed paper container is required to have heat resistance that does not peel off from the substrate even under conditions of heating and expanding the substrate.
[0009] As described above, in the use of foamed paper containers, the substrate expands with the heat processing to form the foam layer. On the other hand, in general uses such as packaging, the substrate is hardly deformed because the heat processing is not performed after the printing layer is formed. Due to such differences, it is difficult to obtain various desired properties such as heat resistance at a sufficiently satisfactory level by simply replacing the ink components for forming the printing layer of the foamed paper container with environmentally friendly inks used in general uses. Therefore, the development of a foamed paper container using a biomass resin is desired, but the adoption of biomass resin has not progressed because special performance is required for foamed paper containers as described above. Therefore, in view of the above situation, an embodiment of the present invention provides a foamed paper laminate having a printing layer containing a biomass resin, which has excellent heat resistance, foaming followability, foaming appearance, and ethanol resistance, and can be suitably used as a component of a foamed paper container. [Means for solving the problem]
[0010] In order to solve the above problems, the present inventors have conducted extensive research into the resin components constituting the printed layer of a foamed paper laminate, and have found that forming a printed layer containing a specific biomass resin provides good results in terms of the properties of the printed layer, such as heat resistance, foaming followability, foaming appearance, and ethanol resistance, thereby completing the present invention. That is, the present invention relates to the following embodiments, but includes various embodiments without being limited thereto.
[0011] One embodiment is a foamed paper laminate comprising a base paper, a foamed paper consisting of a thermoplastic resin layer (A) provided on one side of the base paper, and a foamed thermoplastic resin layer (B) provided on the other side of the base paper, and a printed layer provided on the foamed thermoplastic resin layer (B), The printing layer contains at least a binder resin, The binder resin relates to a foamed paper laminate, which contains a urethane resin having structural units derived from castor oil polyol.
[0012] In one embodiment, the urethane resin preferably further contains a structural unit derived from a polyester polyol, which is a condensate of a dibasic acid and a diol. The mass ratio (a1) / (a2) of the structural unit (a1) derived from the castor oil polyol to the structural unit (a2) derived from the polyester polyol is preferably 75 / 25 to 10 / 90.
[0013] In one embodiment, the content of structural units derived from polyether polyol is preferably 8 mass% or less based on the total mass of the urethane resin.
[0014] In one embodiment, the weight average molecular weight of the castor oil polyol is preferably 1,000 to 5,000.
[0015] In one embodiment, the binder resin further contains a vinyl chloride / vinyl acetate copolymer, and the content of the vinyl chloride / vinyl acetate copolymer is preferably 5 mass % or more and 50 mass % or less based on the total mass of the binder resin.
[0016] In one embodiment, the elongation percentage of the binder resin is preferably 400% to 3,000%. Effect of the Invention
[0017] According to the present invention, it is possible to provide a foamed paper laminate which has a printed layer containing a biomass resin, has excellent heat resistance, foaming followability, foamed appearance, and ethanol resistance, and can be suitably used as a component of a foamed paper container. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a perspective view showing an example of the structure of a foamed paper container having a foamed paper laminate according to one embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an enlarged view of a part (reference symbol I part) of the foamed paper container shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, the embodiments of the present invention will be described in detail. However, the present invention is not limited to the embodiments described below and includes various embodiments.
[0020] <1> Foam paper laminate One embodiment relates to a foamed paper laminate. The foamed paper laminate has a foamed paper having a thermoplastic resin layer (A), a paper base material, and a foamed thermoplastic resin layer (B) in this order, and a printed layer formed on the surface of the foamed thermoplastic resin layer (B) of the foamed paper. The printed layer contains at least a biomass resin as a binder resin, and the biomass resin preferably contains at least a urethane resin derived from biomass. In one embodiment, the binder resin contains a urethane resin having a structural unit derived from castor oil polyol. The urethane resin is a biomass-derived urethane resin obtained by using at least a castor oil polyol as a raw material polyol component. Details of such a biomass-derived urethane resin will be described later.
[0021] In one embodiment, the foamed thermoplastic resin layer (B) has a foam cell number per unit surface area of 1000 cells / 1 cm. 2 It is preferable that the residual rate of the printed layer after immersion in ethanol at 25° C. for 30 minutes is 50% by mass or more.
[0022] The number of foam cells per unit surface area of the foamed thermoplastic resin layer (B) (hereinafter also referred to as the foamed layer (B)) is such that the larger the number, the smaller the bubbles present in the foamed layer (B), and vice versa. If the bubbles present in the foamed layer (B) are large, defects in appearance such as cracks and blisters on the printed surface are likely to occur.
[0023] In one embodiment, the number of foam cells per unit surface area of the foam layer (B) is 1000 cells / 1 cm 2 More than 1250 pieces / 1cm is preferable. 2 It is more preferable that the number of foamed cells is 1600 cells / cm or more. When the number of foamed cells is within the above range, an excellent foamed appearance without cracks or blisters can be easily obtained in the printed layer formed on the foamed layer (B). On the other hand, there is no particular upper limit to the number of foamed cells. In one embodiment, from the viewpoint of production conditions, etc., the number of foamed cells is 1600 cells / cm. 2 It may be the following:
[0024] Here, the "number of foam cells per unit area" refers to the number of closed cells (air bubbles) present within a range of a certain length in the vertical and horizontal (XY) directions on the surface of the foam layer (B), and is calculated as the number of closed cells (air bubbles) present within 1 cm 2 The number of closed cells is determined by removing the printed layer of the foam paper laminate with a solvent to expose the surface of the foam layer (B), and then observing the surface of the foam layer (B) with an optical microscope.
[0025] From the viewpoint of heat insulation, the thickness of the foam layer (B) is preferably 500 μm or more, and more preferably 630 μm or more. If the thickness of the foam layer (B) is 500 μm or more, even when the foam paper laminate is molded into a cup-shaped container and hot water of about 100° C. is poured into the container, it becomes easy to continuously hold the container with bare hands. On the other hand, from the viewpoint of resource saving, it is preferable to use as little resin as possible. Also, from the viewpoint of heat insulation, a thickness that is excessive as a heat insulation layer is not necessary. Therefore, the thickness of the foam layer (B) is preferably 950 μm or less, more preferably 900 μm or less, and extremely preferably 800 μm.
[0026] From the above viewpoints, in one embodiment, the thickness of the foamed layer (B) is preferably 500 to 950 μm, more preferably 500 to 900 μm, and even more preferably 500 to 800 μm. The thickness of the foamed layer (B) is determined by observing the cross section of the foamed paper laminate with an optical microscope photograph and measuring the height from the upper surface of the paper base material to the lower surface of the printing layer.
[0027] In the foamed paper laminate of the above embodiment, the foamed layer (B) of the foamed paper means a state after the thermoplastic resin layer is foamed by heating. That is, the foamed layer (B) is a precursor of an unfoamed thermoplastic resin layer (foamed thermoplastic resin layer forming layer (B 0 In one embodiment, in order to form the foamed paper laminate, a thermoplastic resin layer (A), a paper substrate, and a foamed thermoplastic resin layer-forming layer (B) having a melting point lower than that of the thermoplastic resin layer (A) and foaming by heat treatment are used. 0 ) can be used. The foamed paper material can be made of materials known in the art. The constituent materials of the foamed paper laminate will be specifically described below.
[0028] (Paper base material) The paper base material constituting the foamed paper laminate is not particularly limited. For example, kraft paper or fine paper can be used. In order to achieve sufficient strength when used as a container, the basis weight of the paper base material is 150 to 450 g / m 2 It is preferable that the thickness is 250 to 400 g / m 2 From the viewpoint of obtaining suitable expandability of a thermoplastic resin such as polyethylene, the moisture content in the paper base material is preferably 4 to 10% by mass, and more preferably 5 to 8% by mass.
[0029] (Thermoplastic resin layer, foam layer forming layer) In one embodiment, a thermoplastic resin layer (A) and a foamed thermoplastic resin layer forming layer (B 0 ) (hereinafter referred to as foam layer forming layer (B 0 Each of the thermoplastic resin layers (A) and (B) may be a film made of a resin material that has been conventionally known as a container material. For example, a film (thermoplastic resin film) made of at least one thermoplastic resin selected from the group consisting of oriented and unoriented polyolefins such as polyethylene and polypropylene, polyester, nylon, cellophane, and vinylon can be used. In one embodiment, a polyethylene film can be preferably used because of its excellent lamination suitability and foaming property. Furthermore, from the viewpoint of reducing the environmental load, the thermoplastic resin layer (A) and the foam layer forming layer ... at least one thermoplastic resin material selected from the group consisting of oriented and unoriented polyolefins such as polyethylene, polypropylene, and the like. 0 ) is preferably a film made of a polyethylene resin derived from biomass.
[0030] The foamed paper material can be constructed by laminating thermoplastic resin films having different melting points to a paper substrate. Here, the foamed layer forming layer (B) is formed on one side of the paper substrate rather than the thermoplastic resin film formed on the other side of the paper substrate as the thermoplastic resin layer (A). 0 The material is selected so that the melting point (Mp) of the thermoplastic resin film provided on the other side of the paper substrate as the foam layer (B) is low. In the case of foam paper materials, the water in the paper substrate evaporates during the heat treatment, and the evaporated water is transferred to the softened foam layer forming layer (B 0) (low Mp resin film). As the low Mp resin film is extruded, it expands (foams) outward to form a foamed layer (B). The foamed layer (B) thus formed functions as a heat insulating layer in the container. On the other hand, for the thermoplastic resin layer (A) (high Mp resin film), a material is selected that does not melt or soften when the low Mp resin film foams due to heat treatment.
[0031] From the viewpoint of producing a foamed paper container using the foamed paper laminate, the foamed paper material is, for example, a high Mp polyethylene film (thermoplastic resin layer (A)) having a melting point of about 125°C to 140°C on one side (inside of the container) of the paper base material, and a low Mp polyethylene film (foamed layer forming layer (B)) having a melting point of about 105°C to 120°C on the other side (outside of the container) of the above paper base material. 0 )) may be laminated together. When heated during the production of a foamed paper container, the low Mp polyethylene film foams to form a foamed layer. On the other hand, the high Mp polyethylene film preferably functions as a coating layer. That is, the coating layer suppresses the moisture in the paper substrate from evaporating to the outside during the foaming of the low Mp polyethylene film, and allows the moisture in the paper substrate to efficiently contribute to foaming.
[0032] In one embodiment, the foam layer forming layer (B 0 The material is low-density polyethylene resin (density 910-925 kg / m 3 The density of the low-density polyethylene resin is preferably 910 to 922 kg / m 3 and more preferably 910 to 918 kg / m 3 The foam layer forming layer (B 0 ) is made of medium density polyethylene resin (density 925-940kg / m 3 , melting point 115-130°C), and high density polyethylene resin (density 940-970kg / m 3When a polyethylene resin having a melting point of 125 to 140° C. is used, the melting point is high and it tends to be difficult to obtain sufficient foaming. From the viewpoint of obtaining a uniformly foamed layer, the melt flow rate (hereinafter referred to as "MFR") of the polyethylene resin is preferably 8 to 28 g / 10 min, and more preferably 10 to 20 g / 10 min. In one embodiment, it is preferable to combine a polyethylene film derived from biomass. For example, "SHE150 (density 948 kg / m)" manufactured by Braskem Corporation is used as the thermoplastic resin layer (A). 3 , MFR 1g / 10min) was used, and the foam layer forming layer (B 0 Braskem's SBC818 (density 918kg / m 3 , MFR8.1g / 10min) can be used.
[0033] Although not particularly limited, in one embodiment, the foam layer forming layer (B 0 The thickness of the insulating layer 2 is preferably 40 μm or more, and more preferably 60 μm or more. By adjusting the thickness to 40 μm or more, sufficient heat insulation can be obtained after heat treatment.
[0034] On the other hand, from the viewpoint of resource saving, it is preferable to use as little resin as possible. Also, from the viewpoint of heat insulation, a thickness that is excessive is not necessary. Therefore, the foam layer forming layer (B 0 ) has a thickness of preferably 150 μm or less, more preferably 100 μm or less, and most preferably 80 μm or less.
[0035] (Printing layer) In the foamed paper laminate of the above embodiment, the printing layer is a foamed layer forming layer (B 0The coating film is obtained by applying an ink composition to the surface of a printed paper. The main component of the coating film constituting the printed layer (i.e., the ink composition) is a binder resin, and the binder resin is characterized by containing at least a urethane resin having a structural unit derived from castor oil polyol. By using such a biomass-derived urethane resin, it is possible to realize a foamed paper laminate that is excellent in properties such as heat resistance and foaming followability during heat processing, as well as foamed appearance and ethanol resistance, and that can be suitably used as a component of a foamed paper container.
[0036] In one embodiment, the thickness of the printed layer (coating film after drying) is preferably 0.5 to 5.0 μm from the viewpoint of foam suppression power of the printed layer and abrasion resistance, more preferably 0.5 to 4.0 μm, and further preferably 0.5 to 3.5 μm.
[0037] In the above embodiment, since a biomass-derived urethane resin is used as the binder resin constituting the printing layer, the environmental load can be reduced compared to the case of using a conventional petroleum-derived resin. From this viewpoint, the biomass degree based on the total mass of the binder resin is preferably 10 mass% or more. In another embodiment, the printing layer may contain a colorant and a binder resin. In this case, the biomass degree based on a total of 100 parts by mass of the colorant and the binder resin is preferably 10 mass% or more. From the viewpoint of building a recycling-based society, the higher the biomass degree, the better. Specifically, the biomass degree is more preferably 15 mass% or more.
[0038] In this specification, the term "biomass degree" means the ratio of biomass-derived raw materials in all components used as raw materials. For example, it means the ratio of biomass-derived components in a compound obtained after synthesis of a binder resin. That is, in the case of a biomass-derived component, if the raw materials are all biomass-derived, such as vegetable oil, the biomass degree is 100%. On the other hand, in the case of a compound obtained by reacting a biomass-derived raw material with a non-biomass-derived raw material (e.g., petroleum-derived raw material) in a certain ratio, the ratio of the biomass-derived raw material in the compound is the biomass degree. In this case, the biomass degree can be calculated by converting it into the mass of the raw materials before the reaction, and is a value represented by the following formula (1). Formula (1): Biomass degree = 100 × total mass of biomass-derived components in a compound / total mass of a compound
[0039] More specifically, for example, in the case of a urethane resin that is a reaction product of a biomass-derived polyol (biomass degree A%) and a petroleum-derived diisocyanate, the biomass degree is expressed by the following formula. Biomass ratio = 100 x (mass of biomass-derived polyol x A%) / mass of urethane resin In the above formula, "mass of urethane resin" refers to the sum of the biomass-derived polyol and the petroleum-derived diisocyanate, and "biomass-derived polyol" refers to the sum of all biomass-derived polyols used in the urethane resin.
[0040] In the foamed paper laminate of the above embodiment, at least castor oil polyol is used as the polyol component, so that it is easy to increase the biomass degree. The biomass degree can be measured by measuring the radioactive carbon ( 14 C) concentration. Biomass-derived compounds can also be distinguished from petroleum-derived compounds by their degree of biomass, since petroleum-derived compounds do not have radioactive carbon.
[0041] <2> Ink composition One embodiment relates to an ink composition that can be suitably used to form a printing layer of the foam paper laminate of the above embodiment. The ink composition includes a binder resin including a urethane resin having a structural unit derived from castor oil polyol, and a solvent. In another embodiment, the ink composition may further include a colorant such as a pigment. In addition to the above components, the ink composition may further include various additives as necessary. The composition of the ink composition will be described below.
[0042] (binder resin) During the heat processing to form the foam layer (B), the printing layer is 0 On the other hand, in order to suppress poor appearance due to foaming, such as cracks and blisters on the printed surface, it is preferable that the foaming layer forming layer (B 0 It is preferable that the foaming of the printed layer can be appropriately controlled by the printed layer. On the other hand, since the binder resin is the main component of the printed layer (coating), the foaming followability and foaming suppression power of the printed layer can be well adjusted by selecting an appropriate form of the binder resin.
[0043] From the viewpoint of foaming followability, the binder resin preferably has an elongation rate of 50 to 4,000%, more preferably 400 to 3,000%. On the other hand, even if the binder resin has an elongation rate of 50 to 4,000%, if the stress is excessively small, the printed layer follows the foaming, but the foaming cannot be appropriately controlled, and cracks and blisters occur, which tends to deteriorate the foamed appearance. Therefore, from the viewpoint of achieving both foaming followability and the foamed appearance of the printed surface, the binder resin preferably has an elongation rate of 50 to 4,000% and a stress of 0.1 mPa or more.
[0044] The term "elongation" used in this specification refers to a value obtained by measuring a sample having dimensions of 0.3 mm in thickness and 15 mm in width at a tensile speed of 100 mm / min at room temperature of 25°C using a small tensile tester manufactured by Intesco Corporation.
[0045] In one embodiment, the stress of the binder resin at an elongation rate of 50 to 4,000% is preferably 0.1 mPa or more, more preferably 1 mPa or more, and even more preferably 5 mPa or more. Meanwhile, the stress at an elongation rate of 50 to 4,000% is preferably 50 mPa or less, more preferably 40 mPa or less, and even more preferably 30 mPa or less. The stress of the binder resin containing a urethane resin at an elongation rate of 50 to 4,000% may be 0.1 mPa to 50 mPa.
[0046] When the binder resin has the elongation and stress in the above range, it is easy to obtain good results in terms of foaming appearance as well as foaming followability. In addition, the binder resin having the elongation and stress in the above range is also preferable from the viewpoint of improving ethanol resistance because it is easy to obtain a desired remaining rate of the printed layer.
[0047] (urethane resin) As described above, from the viewpoint of the foaming followability of the printing layer during foaming, the binder resin preferably contains at least a urethane resin. A specific embodiment includes a urethane resin obtained by reacting a polyol with a diisocyanate. Another example includes a urethane urea resin obtained by chain-extending a urethane prepolymer obtained by reacting a polyisocyanate with a polyol with an amine compound. That is, the urethane resin is a resin having a urethane bond, but it is also included in the concept even if it further has a urea bond or the like.
[0048] When urethane resin is used, it has excellent resistance to light, heat, abrasion, and blocking, and is also excellent in the low Mp resin film (foam layer forming layer (B 0)) can be easily constructed. In addition, by using a urethane resin, even when the ink composition is stored for a long period of time in an environment where heat or light is applied, it is possible to obtain good results in various properties such as the abrasion resistance, blocking resistance, and adhesion to the low Mp resin film that serves as the substrate of the printed layer.
[0049] The urethane resin preferably has a weight average molecular weight in the range of 10,000 to 100,000, and more preferably 30,000 to 80,000. When the weight average molecular weight is within the above range, the blocking resistance, solubility in organic solvents, and pigment dispersibility of the printed layer can be easily improved.
[0050] The urethane resin preferably has an amine value. The amine value is preferably 0.5 to 40 mgKOH / g, more preferably 1 to 30 mgKOH / g, and further preferably 3 to 20 mgKOH / g. When the amine value is within the above range, it becomes easy to increase the adhesion.
[0051] In one embodiment, the urethane resin preferably has a glass transition temperature (Tg) of -100°C to 0°C. The Tg of the urethane resin may be more preferably -10°C or less, and further preferably -25°C or less. When the Tg of the binder resin is within the above range, excellent foaming followability can be obtained during the heat treatment of the foamed paper material, and a decrease in heat insulation can be suppressed. In addition, foaming appearance defects such as cracks and blisters on the printed surface can be suppressed. The Tg may be -100°C or more, preferably -90°C or more, more preferably -80°C or more, and even more preferably -60°C or more. A binder resin having a Tg within the above range is also preferable from the viewpoint of ethanol resistance, since it is easy to obtain a desired remaining rate of the printed layer.
[0052] (Urethane resin having structural unit (a1) derived from castor oil polyol) In an embodiment of the present invention, the urethane resin is characterized by using a urethane resin derived from biomass, and includes a urethane resin having at least a structural unit (a1) derived from castor oil polyol. A specific embodiment includes a urethane resin obtained by reacting a polyol containing castor oil polyol with a diisocyanate. Furthermore, a preferred embodiment includes a urethane urea resin obtained by chain-extending a urethane prepolymer obtained by reacting a polyisocyanate with a polyol containing castor oil polyol with an amine compound.
[0053] As the diisocyanate, known aromatic, aliphatic or alicyclic diisocyanates can be used. For example, 1,5-naphthylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-diphenyldimethylmethane diisocyanate, 4,4'-dibenzyl isocyanate, dialkyldiphenylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, tolylene diisocyanate, butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropylene diisocyanate, methylene diisocyanate, diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, xylylene diisocyanate, isophorone diisocyanate, lysine diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, methylcyclohexane diisocyanate, norbornane diisocyanate, m-tetramethylxylylene diisocyanate, dimer diisocyanate in which the carboxyl group of a dimer acid is converted to an isocyanate group, etc. In one embodiment, isophorone diisocyanate is preferred.
[0054] As the polyol, it is essential to use castor oil polyol, but other than that, polyester polyol, polyether polyol, low molecular weight polyhydric alcohol, polycarbonate polyol, etc. can be used. However, all polyols are except for those that fall under castor oil polyol. The polyol component will be described in more detail below. Castor oil polyol The castor oil polyol may have a structural unit derived from ricinoleic acid (hereinafter, castor oil fatty acid), which is a component of castor oil. The structural unit derived from ricinoleic acid is preferably the main component in the total amount of castor oil polyol (50% by mass or more in the total amount of castor oil polyol). The structure is not particularly limited as long as the average number of functional groups of hydroxyl groups is 1 to 3, and examples thereof include castor oil and dehydrated castor oil. Other examples include castor oil fatty acid condensates obtained by condensing castor oil fatty acids with polyols such as diols as an initiator, and hydrogenated products thereof. These castor oil polyols can be used alone or in combination of two or more.
[0055] The urethane resin preferably contains 10 to 80% by mass, more preferably 15 to 60% by mass, and even more preferably 15 to 40% by mass of structural units derived from castor oil polyol relative to the resin solid content of the urethane resin. When the content of the structural units derived from castor oil polyol is within the above range, it is easy to maintain or improve the dispersion stability of the colorant, the heat resistance of the printed layer, and the blocking resistance.
[0056] The molecular weight of the castor oil polyol is preferably a weight average molecular weight of 500 to 6,000, more preferably 1,000 to 5,000, further preferably 1,500 to 4,000, and particularly preferably 1,500 to 3,500. When the weight average molecular weight is within the above range, excellent coating strength is obtained when a foamed paper laminate is formed, and the foamed layer forming layer (B 0 ) can be easily obtained.
[0057] Polyester polyol The urethane resin preferably contains a structural unit derived from polyester polyol in addition to the structural unit derived from castor oil polyol.In the study by the present inventors, it was found that when the urethane resin obtained by using castor oil polyol and polyester polyol in combination is used as the binder resin of the printing layer, it tends to obtain better foaming appearance and heat resistance than when the urethane resin obtained by using only castor oil polyol is used alone.
[0058] Examples of the polyester polyol include, but are not limited to, dibasic acids such as adipic acid, phthalic anhydride, isophthalic acid, terephthalic acid, maleic acid, fumaric acid, succinic acid, oxalic acid, malonic acid, pimelic acid, azelaic acid, sebacic acid, suberic acid, glutaric acid, and 1,4-cyclohexyldicarboxylic acid; and polyols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, neopentyl glycol, Examples of the polyester polyols include condensates obtained by esterification with diols such as 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 3,3,5-trimethylpentanediol, 2,4-diethyl-15-pentanediol, 1,12-octadecanediol, 1,2-alkanediol, 1,3-alkanediol, 1-monoglyceride, 2-monoglyceride, 1-monoglycerin ether, and 2-monoglycerin ether, and polyester diols such as caprolactone polymers, valerolactone polymers, methylvalerolactone polymers, and lactic acid polymers obtained using the diol of the present invention as an initiator. These polyester polyols can be used alone or in combination of two or more.
[0059] From the viewpoints of heat resistance, coating strength, and blocking resistance in the laminate, the amount of polyester polyol used is preferably 15 to 80 mass% of structural units derived from polyester polyol relative to the resin solid content of the urethane resin, and more preferably 25 to 75 mass%.
[0060] In one embodiment, the urethane resin preferably has a structural unit derived from a polyester polyol in addition to a structural unit derived from a castor oil polyol. The polyester polyol is a condensate of the dibasic acid and the diol, and the mass ratio (a1) / (a2) of the structural unit (a1) derived from the castor oil polyol to the structural unit (a2) derived from the polyester polyol is preferably 75 / 25 to 10 / 90, more preferably 60 / 40 to 25 / 75, and even more preferably 50 / 50 to 25 / 75. By adjusting the mass ratio in this way, it is possible to easily improve the foaming followability, heat resistance, and ethanol resistance.
[0061] In one embodiment, the binder resin includes a urethane resin obtained by using only castor oil polyol as the polyol component. In another embodiment, the binder resin includes a urethane resin obtained by using castor oil polyol and polyester polyol in combination as the polyol component. In still another embodiment, the binder component may include the urethane resin of the above embodiment and a urethane resin obtained by using only polyester polyol as the polyol component. However, when polyester polyol is used as the polyol component, it is more preferable that the structural unit derived from castor oil polyol and the structural unit derived from polyester polyol coexist in one polymer chain from the viewpoint of ink stability and the like.
[0062] <Polyether polyol> In one embodiment, the urethane resin may have a structural unit derived from polyether polyol. The polyether polyol is not particularly limited, but may be, for example, polyethylene glycol, polypropylene glycol, polytrimethylene glycol, polytetramethylene glycol, or copolymer polyether diols thereof. These polyether polyols may be used alone or in combination of two or more.
[0063] By introducing a structural unit derived from polyether polyol into the urethane resin, it is possible to adjust various physical properties required for a resin for printing ink, such as pigment dispersibility, resin viscosity, and solubility in organic solvents. On the other hand, in the study by the present inventors, it has been found that if there are too many structural units derived from polyether polyol, the heat resistance, which is an essential characteristic of the printing layer of the foamed paper laminate, decreases. From this viewpoint, in one embodiment, based on the total mass of the urethane resin, the content of the structural unit derived from polyether polyol is preferably 8 mass% or less, more preferably 5 mass% or less, further preferably 2 mass% or less, and may be 0 mass%. From the viewpoint of improving the heat resistance of the printing layer, it is extremely preferable that the urethane resin does not contain a structural unit derived from polyether polyol.
[0064] <Low molecular weight polyhydric alcohol> In one embodiment, the urethane resin may have a structural unit derived from a low molecular weight polyhydric alcohol. By introducing a structural unit derived from a low molecular weight polyhydric alcohol, it is possible to adjust various physical properties required for a resin for printing inks, such as pigment dispersibility, resin viscosity, solubility in organic solvents, and blocking resistance.
[0065] Examples of low molecular weight polyhydric alcohols include, but are not limited to, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, butylene glycol, hexylene glycol, neopentyl glycol, cyclohexanedimethanol, glycerin, 1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, hydrogenated bisphenol A, trimethylolpropane, glycerin, pentaerythritol, and sorbitol. These low molecular weight polyhydric alcohols are used for the purpose of adjusting the molecular weight of the ink composition of the present invention and the distribution of hard and soft segments. These low molecular weight polyhydric alcohols can be used alone or in combination of two or more.
[0066] Amine compounds The amine compound functions as a chain extender for the urethane prepolymer, and gives a urea bond to the urethane resin. Examples of the amine compound include polyamines and amino alcohols. The chain extender can be used alone or in combination of two or more kinds.
[0067] Examples of polyamines include ethylenediamine, propylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, dimer diamine in which the carboxyl groups of dimer acid are converted to amino groups, and the like; as well as amines having a hydroxyl group in the molecule, such as N-(2-hydroxyethyl)ethylenediamine, N-(2-hydroxyethyl)propylenediamine, N-(2-hydroxypropyl)ethylenediamine, N-(2-hydroxypropyl)propylenediamine, N,N'-bis(2-hydroxyethyl)ethylenediamine, N,N'-bis(2-hydroxyethyl)propylenediamine, N,N'-bis(2-hydroxypropyl)ethylenediamine, and N,N'-bis(2-hydroxypropyl)propylenediamine; and amines having a tertiary amino group in the molecule, such as methyliminobispropylamine and lauryliminobispropylamine.
[0068] Examples of amino alcohols include N,N-dimethylethanolamine, N,N-dimethylethanolamine, N,N-dibutylethanolamine, N-(β-aminoethyl)ethanolamine, N-methylethanolamine, N-methyldiethanolamine, N-ethylethanolamine, N-ethyldiethanolamine, Nn-butylethanolamine, Nt-butyldiethanolamine, Nt-butyldiethanolamine, N-(β-aminoethyl)isopropanolamine, and N,N-diethylisopropanolamine.
[0069] <Reaction Solvent> In producing the urethane resin, an alcohol and / or an organic solvent having no hydroxyl group, which is a medium described later, can be used.
[0070] Examples of the alcohol include aliphatic alcohols having 1 to 7 carbon atoms, such as methanol, ethanol, normal propanol, isopropanol, normal butanol, isobutanol, and tertiary butanol; and glycol monoethers, such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monoisopropyl ether, and propylene glycol monobutyl ether. When producing a prepolymer solution containing an isocyanate group, from the viewpoint of reactivity with the isocyanate group, a tertiary alcohol having low reactivity is preferred, such as tertiary butanol.
[0071] Examples of organic solvents having no hydroxyl group include esters such as ethyl acetate, butyl acetate, cellosolve acetate, etc., ketones such as acetone, methyl ethyl ketone, isobutyl ketone, cyclohexanone, etc., cyclic ethers such as tetrahydrofuran, dioxane, etc., aromatic hydrocarbons such as toluene, xylene, etc., halogenated hydrocarbons such as methylene chloride, ethylene chloride, etc., dimethyl sulfoxide, dimethyl sulfamide, etc. Two or more of these reaction solvents may be mixed and used.
[0072] <Production of urethane resin> The method for producing the urethane resin is not particularly limited, and the resin can be produced by a general chain extension reaction. For example, a prepolymer containing an isocyanate group is produced by reacting a castor oil polyol, a polyol other than castor oil polyol, and a diisocyanate in the absence of a solvent or in an organic solvent having no hydroxyl group. Here, the reaction is carried out at an equivalent ratio in which the isocyanate group of the diisocyanate is in excess relative to the hydroxyl groups of the castor oil polyol and the polyol other than castor oil polyol. The prepolymer containing an isocyanate group obtained as described above is dissolved in an organic solvent having no hydroxyl group and / or a tertiary alcohol having low reactivity with an isocyanate group to obtain a prepolymer solution. Next, a method is available in which the previously prepared prepolymer solution containing an isocyanate group is added to a solution in which a chain extender is dissolved in a solvent to carry out a chain extension reaction.
[0073] The solvent used to dissolve the chain extender may be the same as the organic solvent used in the production of the prepolymer. When alcohol is used as the solvent, it is preferable to use diamines or aminoalcohols as the chain extender from the viewpoint of reactivity with the isocyanate group-containing prepolymer.
[0074] In the production of urethane resin, the ratio of castor oil polyol, polyol other than castor oil polyol, and diisocyanate is preferably adjusted so that the NCO / OH ratio, which is the ratio of the molar number of isocyanate groups of diisocyanate to the molar number of hydroxyl groups of castor oil polyol and polyol other than castor oil polyol, is in the range of 1.1 to 3.0. When the NCO / OH ratio is within the above range, it is easy to maintain or improve blocking resistance and substrate adhesion.
[0075] In the above embodiment, the printing layer is characterized by including a urethane resin as a component, but this does not exclude the use of a binder resin other than the urethane resin.Specific examples of suitable binder resins include acrylic resin, vinyl chloride resin, vinyl acetate resin, vinyl chloride / vinyl acetate copolymer, and nitrocellulose.
[0076] Among them, a combination of a urethane resin and a vinyl chloride / vinyl acetate copolymer and / or nitrocellulose is preferred. When the binder resin further contains a vinyl chloride / vinyl acetate copolymer, it is preferred that the binder resin contains 50% by mass or more of the urethane resin based on the total mass of the binder resin. The content is more preferably 70% by mass or more, and even more preferably 85% by mass or more. The mass ratio of the urethane resin containing the urethane resin and the vinyl chloride / vinyl acetate copolymer is preferably 40:60 to 95:5, more preferably 55:45 to 90:10, and extremely preferably 70:30 to 90:10. By adjusting the mass ratio of the two within the above range, the foam paper conformability and heat resistance can be easily improved.
[0077] (Coloring agent) In one embodiment, the ink composition may further include a colorant. The colorant may be, for example, an organic pigment, an inorganic pigment, a dye, or the like, which is used in ordinary ink compositions. CI pigments listed in the Color Index can be suitably used.
[0078] Suitable examples of organic pigments include azo-based, phthalocyanine-based, anthraquinone-based, perylene-based, perinone-based, quinacridone-based, thioindigo-based, dioxazine-based, isoindolinone-based, quinophthalone-based, azomethine azo-based, dicyanopyrrolopyrrole-based, and isoindoline-based pigments.
[0079] Examples of inorganic pigments include carbon black, aluminum powder, bronze powder, chrome vermilion, yellow lead, cadmium yellow, cadmium red, ultramarine, Prussian blue, iron oxide red, yellow iron oxide, iron black, titanium oxide, and zinc oxide.
[0080] Examples of dyes include tartrazine lake, rhodan 6G lake, Victoria Pure Blue Lake, Alkaline Blue G Toner, Brilliant Green Lake, etc. In addition, coal tar, etc. can also be used. Among them, it is preferable to use organic pigments or inorganic pigments from the viewpoint of water resistance, etc.
[0081] The colorant is not particularly limited, and may be used in an amount sufficient to ensure the concentration and coloring power of the ink composition. For example, the content of the colorant is generally 0.5 to 50 mass% based on the total mass of the ink composition. The colorant may be used alone or in combination of two or more kinds.
[0082] In one embodiment, when preparing a white ink composition, the amount of the white pigment is preferably in the range of 20 to 50% by mass based on the total mass of the ink composition. From the viewpoints of hiding power, pigment concentration, and light resistance, it is preferable to use titanium dioxide as the white pigment. On the other hand, when preparing a colored ink composition, a colored organic pigment and a colored inorganic pigment such as red iron oxide, Prussian blue, ultramarine, carbon black, graphite, etc. can be appropriately selected and used. From the viewpoints of color development and light resistance, organic pigments are preferred. The amount of the colored pigment is preferably in the range of 5 to 30% by mass based on the total mass of the ink composition.
[0083] (Organic solvents as ink media) In one embodiment, the ink composition contains an organic solvent as a liquid medium. Although not limited to the following, the organic solvent used may be an aromatic organic solvent such as toluene or xylene, a ketone organic solvent such as methyl ethyl ketone or methyl isobutyl ketone, an ethyl acetate, n-propyl acetate, isopropyl acetate, isobutyl acetate, an ester organic solvent, an alcohol organic solvent such as methanol, ethanol, n-propanol, isopropanol, or n-butanol, or a glycol ether solvent such as ethylene glycol monopropyl ether or propylene glycol monoethyl ether, or may be used in combination. Among them, an organic solvent that does not contain an aromatic organic solvent such as toluene or xylene (non-toluene organic solvent) is more preferable. Furthermore, due to the compatibility of the urethane resin and the vinyl chloride copolymer resin, an organic solvent containing an ester organic solvent and an alcohol organic solvent is preferable, and the mass ratio of these (ester organic solvent) / (alcohol organic solvent) is preferably 90 / 10 to 40 / 60. The gravure ink may contain water as a liquid medium, and the content thereof is preferably 0.1 to 5% by mass in 100% by mass of the liquid medium.
[0084] (Additives) The ink layer and the ink composition may contain additives, such as pigment derivatives, dispersants, wetting agents, adhesion aids, leveling agents, defoamers, antistatic agents, viscosity modifiers, chelating crosslinking agents, trapping agents, antiblocking agents, wax components, isocyanate-based curing agents, and silane coupling agents, if necessary.
[0085] <Method of producing ink composition> The ink composition can be produced by a known method, for example, the method described in International Publication No. 2009 / 119800. More specifically, a urethane resin, a vinyl chloride / vinyl acetate copolymer, and an organic solvent having a mass ratio of (ester-based organic solvent) / (alcohol-based organic solvent) of 90 / 10 to 40 / 60 are dispersed in a sand mill or other bead mill for about 5 to 60 minutes, and the urethane resin, the organic solvent, a leveling agent and other additives are further added to the obtained dispersion, followed by stirring uniformly to obtain an ink composition.
[0086] <3> Manufacturing method of foamed paper laminate One embodiment relates to a method for producing a foamed paper laminate. That is, one embodiment relates to a method for producing a foamed paper laminate having a foamed paper having a thermoplastic resin layer (A), a paper base material, and a foamed layer (B) in this order, and a printed layer formed on the surface of the foamed layer (B) of the foamed paper. More preferably, in the configuration of the foamed paper laminate, the number of foamed cells per unit surface area of the foamed layer (B) is 1000 cells / 1 cm. 2 The present invention relates to a method for producing a foamed paper laminate in which the remaining rate of the printed layer after immersion in ethanol at 25° C. for 30 minutes is 50% by mass or more.
[0087] The method for producing a foamed paper laminate includes the following steps (i) to (iv): (i) A thermoplastic resin layer (A), a paper substrate, and a foam layer-forming layer (B) having a melting point lower than that of the thermoplastic resin layer (A) and foaming upon heating. 0 providing a foamed paper material having, in sequence, (ii) preparing an ink composition comprising a binder resin containing a urethane resin and a medium; (iii) the foam layer forming layer (B 0 ) applying the ink composition to a surface of the substrate to form a printed layer; (iv) heating the foamed paper material having the printed layer to form the foamed layer forming layer (B 0 ) to form a foamed layer (B). Includes.
[0088] In the above-mentioned manufacturing method, each step of (i) preparing a foamed paper material, (ii) preparing an ink composition, (iii) forming a printed layer, and (iv) forming a foamed layer (B) by heating can be carried out according to a method well known in the art. Each step will be described below.
[0089] (Step (i): Preparation of foam paper material) (i) The preparation of the foamed paper material can be carried out, for example, according to the extrusion lamination method. The foamed paper material is composed of a paper substrate, a thermoplastic resin layer (A), and a foamed layer forming layer (B). 0 The constituent materials of the thermoplastic resin layer (A) and the foam layer forming layer (B) are as described above. As the extrusion lamination method, a well-known method such as a single lamination method, a tandem lamination method, a sandwich lamination method, and a coextrusion lamination method can be appropriately selected. In one embodiment, the thermoplastic resin layer (A) and the foam layer forming layer (B) are 0 As the constituent materials of the first and second layers, polyethylene resins each having a different melting point can be suitably used.
[0090] Foam layer forming layer (B 0 ) is constructed using a polyethylene resin (low Mp polyethylene resin) having a melting point (Mp) lower than the melting point (Mp) of the polyethylene resin constituting the thermoplastic resin layer (A). The foamed paper material can be produced by extruding a low Mp polyethylene resin in the form of a film onto one side of a paper substrate through a T-die extruder, and extruding a high Mp polyethylene resin in the form of a film onto the other side of the paper substrate.
[0091] The temperature of the polyethylene resin during lamination (the temperature immediately below the T-die) is preferably 300 to 350° C., more preferably 320 to 340° C. Within this temperature range, each polyethylene resin layer (A, B 0 It is preferable to control the surface temperature of the cooling roll, which is passed through after lamination, in the range of 10 to 50°C.
[0092] In one embodiment, the lamination speed is preferably 50 to 130 m / min, more preferably 60 to 110 m / min. If the lamination speed is too slow, the productivity is low, while if the lamination speed is too fast, the yield tends to decrease due to neck-in. Neck-in is a phenomenon in which the width of the extruded polyethylene resin film becomes smaller than the effective width of the T-die when polyethylene resin is extruded into a film by a T-die extruder. At this time, both ends of the film become thicker than the center. When the thickness of both ends deviates from the standard, both ends are generally cut and removed, but when the neck-in is severe, the area that deviates from the standard increases, resulting in a decrease in yield.
[0093] In one embodiment, the air gap is preferably 300 mm or less, more preferably 200 mm or less. If the air gap is too wide, the polyethylene resin tends to neck in and the yield tends to decrease. The air gap refers to the distance from the extrusion opening of the T-die to the nip roll. While the polyethylene resin passes through the air gap, it is preferable to perform a surface treatment of the polyethylene resin using ozone gas and / or oxygen gas. By performing the surface treatment using ozone gas and / or oxygen gas, it is possible to promote the formation of an oxide film and improve the adhesive strength with the base layer. There is no particular limitation on the amount of ozone gas and / or oxygen gas to be treated, but from the viewpoint of promoting the oxidation of the polyethylene resin, it is preferable to perform a surface treatment of the polyethylene resin using ozone gas and / or oxygen gas using ozone gas and / or oxygen gas. 2 The above is preferred.
[0094] (Step (ii): Preparation of ink composition) The specific configuration, production, etc. of the ink composition are as described above in the embodiment of the ink composition. In one embodiment, it is preferable to prepare an ink composition containing a binder resin including a urethane resin and a medium. Here, the binder resin is a urethane resin produced using at least castor oil polyol as a polyol component. Such a biomass-derived urethane resin preferably has a stress of 0.1 mPa to 50 mPa at an elongation rate of 50 to 4,000%.
[0095] (Step (iii): Formation of printed layer) The formation of the above (iii) printing layer is not particularly limited, and a well-known technique can be applied. For example, a foam layer forming layer (B 0 When printing a white ink composition on the entire surface of the low Mp resin film, a coater such as a bar coater, a roll coater, or a reverse roll coater may be used. In addition, various printing methods can be used.
[0096] Among various printing methods, it is preferable to apply a printing method by gravure printing or flexographic printing. When forming a printed layer by these printing methods, the ink composition of the embodiment described above can be suitably used.
[0097] In one embodiment, the printing layer preferably includes a plurality of layers. The printing layer includes a foam layer forming layer (B 0 and a printing pattern provided on at least a part of the surface of the underlayer. For example, the underlayer is made of a white ink composition, and the printing pattern is formed of a color ink composition.
[0098] In one embodiment, the thickness of the printed layer is preferably adjusted so that the film thickness of the dry coating is 0.5 to 5 μm from the viewpoint of the foaming suppression power and abrasion resistance of the printed layer. The film thickness of the printed layer (dry coating) may be more preferably 0.5 to 4 μm, and further preferably 0.5 to 3.5 μm. Here, when the printed layer is composed of a plurality of layers, the film thickness of the printed layer is preferably adjusted so that the thickness of the entire printed layer is within the above range.
[0099] In another embodiment, the printing layer may include multiple layers and may have a transparent layer as its outermost layer. The transparent layer may be constructed using a clear ink composition that does not contain a pigment.
[0100] (Step (iv): Formation of foam layer (B)) In the above (iv) formation of the foam layer (B) by heating, the appropriate heating temperature and heating time vary depending on the characteristics of the paper substrate and the thermoplastic resin film used. Those skilled in the art can determine the optimal combination of heating temperature and heating time depending on the material used, such as the thermoplastic resin film. Although not particularly limited, the heat treatment is generally performed in the molding process of the container. If the heating temperature during the heat treatment is too low, sufficient foaming cannot be obtained, and if the heating temperature is too high, the foam cells are bonded and fire blisters are likely to occur.
[0101] Although not particularly limited, when the foam-forming layer is made of a low-density polyethylene film, the heating temperature may be preferably 100 to 125°C, more preferably 110 to 120°C. The heating time can be appropriately adjusted according to the heating temperature, but is preferably 3 to 10 minutes, more preferably 5 to 7 minutes. In one embodiment, when the foam-forming layer is made of a low-density polyethylene film and a printing layer is formed thereon using the ink composition (ii) described above, it is preferable to adjust the heating temperature to 110 to 123°C and the heating time to 5 to 7 minutes. It is more preferable to adjust the heating temperature to 115 to 121°C and the heating time to 5 to 7 minutes. When heating is performed under the above conditions, it becomes easy to appropriately control the foaming of the foam-forming layer during heat processing by the printing layer.
[0102] Any heating means can be used, such as hot air, electric heat, electron beams, etc. If heating is performed by hot air or electric heat in a tunnel equipped with a conveyor transport means, a large amount of heat treatment can be performed inexpensively.
[0103] <4> Foam paper containers One embodiment relates to a foamed paper container having the foamed paper laminate of the above embodiment. The foamed paper container is composed of a container body member and a bottom plate member, and the container body member is characterized in that it is formed from the foamed paper laminate of the above embodiment. Fig. 1 is a perspective view showing the structure of a foamed paper container 10A obtained by carrying out a heat treatment after assembling and molding the container. As shown in Fig. 1, the foamed paper container 10A is composed of a container body member 10 composed of a foamed paper laminate and a bottom plate member 12. In the container body member (foamed paper laminate) 10, the high Mp resin film forms the inner wall surface 10a of the container, and the printed layer on the low Mp resin film (foamed layer) forms the outer wall surface 10b of the container.
[0104] Figure 2 is a schematic cross-sectional view showing an enlarged view of the portion indicated by reference symbol I of the container body member of the foamed paper container shown in Figure 1. The container body member (foamed paper laminate) 10 has, in order from the inner wall surface 10a side of the container (see Figure 1), a high Mp resin film 20, a paper base material 30, a foamed low Mp resin film (foamed layer) 40, and a printed layer 50, and the printed layer 50 has a base layer 50a and a printed pattern 50b.
[0105] The forming of a foamed paper container can be carried out by applying well-known techniques. For example, a foamed paper laminate (foamed paper laminate before heating) on which a print layer is formed is first punched into a predetermined shape along a die to obtain a container body member. Similarly, a bottom plate material is punched into a predetermined shape to obtain a bottom plate member. Next, a commonly used container manufacturing device is used to assemble and mold the container body member and the bottom plate member into the shape of a container. The assembly and molding of the container by the container manufacturing device is carried out so that the high Mp resin film of the container body member forms the inner wall surface, the low Mp resin film forms the outer wall surface, and further the laminate surface of the bottom plate member is on the inside. After the container is assembled and molded by the container manufacturing device in this way, a heat treatment is performed, whereby the low Mp resin film foams to form a foamed layer (thermal insulation layer), and a thermally insulating foamed paper container can be obtained.
[0106] In one embodiment, when the inner wall surface and the outer wall surface of the body of the foamed paper container are each composed of a polyethylene film, it is preferable that one side of the paper base material (the inner wall surface of the container) is laminated with a medium or high density polyethylene film, and the other side (the outer wall surface of the container) is laminated with a low density polyethylene film. The thickness of each film laminated to the paper base material is not particularly limited. However, it is preferable that the thickness of the low Mp resin film constituting the outer wall surface of the container body is appropriately set so that when the film is foamed, the film after foaming is thick enough to function as a heat insulating layer.
[0107] For example, when the outer wall surface of the container body is made of a low-density polyethylene film, the thickness of the film laminated to the paper substrate may be 40 to 150 μm. On the other hand, when the inner wall surface of the container body is made of a medium-density or high-density polyethylene film, the thickness of the film laminated to the paper substrate is not particularly limited. However, it is preferable to appropriately set the thickness of the film so that the permeation resistance of the contents is ensured when used as a heat-insulating foamed paper container. The thickness of the film laminated to the paper substrate varies depending on the resin material of the film used, so it is desirable for a person skilled in the art to appropriately set the thickness in consideration of the characteristics of the resin material. EXAMPLES
[0108] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following, "parts" and "%" represent "parts by mass" and "% by mass" unless otherwise noted.
[0109] <1> Binder Resin (1) Urethane resin raw materials (castor oil polyol and other raw materials) The castor oil polyols used in the synthesis of the following urethane resins are various commercially available polyols and polyols synthesized according to the known method described in JP 2005-320437 A. Among the raw materials described below, raw materials not described as "biomass-derived" are not biomass-derived raw materials.
[0110] (Castor oil polyol 1) "URIC HF-2009" manufactured by Ito Oil Mills (biomass-derived polyol with a weight-average molecular weight of 2,600 and a functional group of 2, whose main component is a structure derived from ricinoleic acid) was used as is.
[0111] (Castor oil polyol 2) "URIC H-57" manufactured by Ito Oil Mills (biomass-derived polyol with a weight-average molecular weight of 1,700 and a structure derived from ricinoleic acid as the main component, functional group number 3) was used as is.
[0112] (Castor oil polyol 3) 100 parts of refined castor oil and 0.57 g of potassium hydroxide (KOH) were placed in a pressure vessel, and the temperature was raised to 110°C by dehydration under reduced pressure. 200 parts of propylene oxide were added to the vessel under a reaction pressure of 4 kg / cm 2 The reaction was continued until the pressure effect was no longer observed. 0.91 g of phosphoric acid was added to the reaction product to neutralize the catalyst, and the reaction product was dehydrated and filtered to obtain a polyol (biomass-derived castor oil polyol 3) with a hydroxyl value of 58 mgKOH / g. The weight average molecular weight measured by GPC was 3,400.
[0113] (Castor oil polyol 4) "URIC H-73X" manufactured by Ito Oil Mills (biomass-derived polyol with a weight-average molecular weight of 600 and a structure derived from ricinoleic acid as the main component, functional group number of 3) was used as is.
[0114] (Castor oil polyol 5) 100 parts of refined castor oil and 0.85 g of KOH were placed in a pressure vessel, and the temperature was raised to 110°C by dehydration under reduced pressure. 284 parts of propylene oxide were added to the vessel under a reaction pressure of 4 kg / cm. 2The reaction was continued until the pressure effect was no longer observed. 1.36 g of phosphoric acid was added to the reaction product to neutralize the catalyst, and the product was dehydrated and filtered to obtain a polyol (biomass-derived castor oil polyol 5) with a hydroxyl value of 45 mgKOH / g. The weight average molecular weight measured by GPC was 5,000.
[0115] (MPD / AA) A polyester polyol made by Kuraray Co., Ltd. and consisting of 3-methyl-1,5-pentanediol and adipic acid and having a weight average molecular weight of 2,000 was used.
[0116] (MPD / SA) A polyester polyol with a weight average molecular weight of 2,000, manufactured by Kuraray Co., Ltd. and consisting of 3-methyl-1,5-pentanediol and sebacic acid (derived from biomass), was used.
[0117] (2) Synthesis example of binder resin (urethane resin) (Synthesis Example 1) [Urethane resin PU1] 30 parts of castor oil polyol 1, 70 parts of a polyester polyol (hereinafter referred to as "MPD / SA") having a weight average molecular weight of 2,000 consisting of 3-methyl-1,5-pentanediol and sebacic acid (derived from biomass), 2.0 parts of 1,3-propanediol (derived from biomass), and 27.4 parts of isophorone diisocyanate (hereinafter referred to as "IPDI") were reacted under a nitrogen stream at 80°C for 5 hours to obtain a resin solution of a urethane prepolymer containing terminal isocyanate groups. Next, 6.2 parts of isophoronediamine (hereinafter "IPDA"), 2.0 parts of iminobispropylamine (hereinafter "IBPA"), 1.0 part of N-(2-hydroxyethyl)ethylenediamine (hereinafter "AEA"), and 323.4 parts of a mixed solvent of ethyl acetate / 2-propanol (hereinafter "IPA") = 60 / 40 (mass ratio) were mixed, and the resin solution of the isocyanate-terminated urethane prepolymer prepared above was gradually added at 40°C, and then the reaction was carried out at 80°C for 1 hour, resulting in a urethane resin solution PU1 (solids content 30%) with a weight average molecular weight of 65,000.
[0118] The weight average molecular weight of the urethane resin was measured as follows. (Weight average molecular weight) As a pretreatment, all amino groups at both ends of the urethane resin were reacted with α,α-dimethyl-3-isopropenylbenzyl isocyanate.Then, the polystyrene-equivalent molecular weight of the pretreated urethane resin was obtained using a Shodex GPC LF-604 (Shodex) column and a gel permeation chromatography (GPC Shodex, GPC-104) equipped with an RI detector, using tetrahydrofuran (THF) as the developing solvent.
[0119] (Synthesis Examples 2 to 12) [Urethane resin PU2~PU12] Urethane resins PU2 to PU12 were obtained in the same manner as in Synthesis Example 1, except that the materials shown in Table 1 were used instead. Details of the synthesis are shown in Table 1.
[0120] (Synthesis Example 13) [Urethane resin PU13] 100 parts of MPD / SA (biomass-derived), 2.0 parts of 1,3-propanediol (biomass-derived), and 25.5 parts of IPDI were reacted at 80°C for 5 hours under a nitrogen stream to obtain a resin solution of terminal isocyanate urethane prepolymer. The resin solution of terminal isocyanate urethane prepolymer obtained was gradually added at 40°C to a mixture of 6.6 parts of IPDA and 317.6 parts of a mixed solvent of ethyl acetate / IPA = 60 / 40 (mass ratio), and then reacted at 80°C for 1 hour to obtain a urethane resin solution PU13 (solid content 30%). The weight average molecular weight of the urethane resin was 68,000.
[0121] (Synthesis Example 14) [Urethane resin PU14] A urethane resin solution PU14 (solid content 30%) was obtained in the same manner as in Synthesis Example 13, except that 100 parts of polyether polyol was used instead of MPD / SA (derived from biomass) as the polyol component. The weight average molecular weight of the urethane resin was 62,000.
[0122] [Table 1]
[0123] (3) Growth rate of binder resin Each urethane resin, vinyl chloride / vinyl acetate copolymer (vinyl chloride / vinyl acetate resin), and nitrocellulose obtained in the above synthesis examples were mixed in the ratios shown in Table 2, and then coated and dried to prepare coating film test samples 1 to 22 (thickness 0.30 mm, width 5.0 mm, length 20.0 mm). The elongation of each sample was measured using a small tensile tester manufactured by Intesco. The measurements were carried out under conditions of a tensile speed of 100 mm / min and a room temperature of 25°C. The results are shown in Table 2.
[0124] [Table 2]
[0125] <2> Production examples of ink compositions (Ink example 1) [Preparation of gravure ink W1] Thirty parts of urethane resin solution PU1 (solid content 30%), 5 parts of vinyl chloride-vinyl acetate copolymer resin (Solvine TAO: copolymer resin manufactured by Nissin Chemical Industry Co., Ltd. with vinyl chloride / vinyl acetate / vinyl alcohol = 91 / 2 / 7 (mass ratio), 30% solid content in ethyl acetate solution)), 30 parts of titanium oxide (manufactured by Teika Corporation Titanix JR-805) as a white pigment, 20.0 parts of n-propyl acetate, and 15 parts of IPA were mixed and dispersed for 30 minutes using an Eiger mill to obtain gravure ink W1.
[0126] (Ink Examples 2 to 21, Comparative Ink Example 1) [Preparation of gravure inks W2 to W20, Blue1, and T1] Gravure inks W2 to W20, Blue1, and T1 were obtained in the same manner as in Example 1, except that the raw materials and compositions were changed as shown in Table 3. The abbreviations in the table stand for the following. In the table, values without a unit notation represent parts, and blanks indicate that no blend was used. Solvine TA3: Vinyl chloride-vinyl acetate copolymer resin with hydroxyl groups (manufactured by Nissin Chemical Industry Co., Ltd., vinyl chloride / vinyl acetate / hydroxyalkyl acrylate = 83 / 4 / 13 (mass ratio)) 30% solids in ethyl acetate solution Nitrocellulose (hereinafter referred to as "NC"): Nitrocellulose 1 / 8H (manufactured by Asahi Kasei Corporation) mixed and dissolved in 30 parts of ethyl acetate and 40 parts of IPA, 30% solids nitrocellulose solution (derived from biomass) CI Pigment Blue 15:3: Lionor Blue FG7330 (Toyo Color Co., Ltd.)
[0127] In addition, when the gravure ink W1 and the gravure ink W20 were left to stand for one week under the condition of 40°C, it was confirmed that the gravure ink W1 was better in terms of the stability (layer separation) of the ink. The gravure ink W1 is an ink using PU1 (a urethane resin having a structural unit derived from castor oil polyol and a structural unit derived from polyester polyol in one polymer chain). On the other hand, the gravure ink 20 is an ink using PU8 (a urethane resin having a structural unit derived from castor oil polyol) and PU14 (a urethane resin having a structural unit derived from polyester polyol) in combination. Therefore, from the viewpoint of the stability of the ink, it is found that the urethane resin in which the structural unit derived from castor oil polyol and the structural unit derived from polyester polyol coexist in the polymer chain is a preferable form.
[0128] [Table 3]
[0129] <4> Manufacturing example of foamed paper laminate (1) Manufacturing example of foam paper material The foamed paper material was produced by (step 1) extrusion laminating a medium-density polyethylene resin (M) to one side of a paper substrate to form a water vapor barrier layer, and then (step 2) extrusion laminating a low-density polyethylene resin (L) to the other side (non-laminated side) of the paper substrate.
[0130] The various conditions in steps 1 and 2 are as follows. (Process 1) Paper base material: moisture content 23kg / m 3 , basis weight 300kg / m 3 Medium density polyethylene resin (M): Tosoh Corporation's "Petrothene LW04-1", MFR 4.3g / 10min, density 940kg / m 3 Extrusion temperature (T die exit temperature): 320℃ Take-off speed (lamination speed): 50m / min Air gap: 130mm Thickness: 40 μm (thickness of the center part of the polyethylene resin layer)
[0131] (Process 2) Low density polyethylene resin (L); see below Extrusion temperature (T die exit temperature): 310℃ Take-off speed (lamination speed): 60m / min Air gap: 130mm Thickness: 50μm
[0132] The low-density polyethylene resin (L) used in the above step 2 is a foam layer forming layer (B 0 ) As the low-density polyethylene resin (L), low-density polyethylene resins (L2) and (L3) were used in Examples 23 and 24 and Comparative Example 2, and low-density polyethylene resin (L1) was used in the other cases to produce the foamed paper material. Details of the low-density polyethylene resins (L1), (L2) and (L3) are as follows. Low-density polyethylene resin (L1): Tosoh Corporation's "Petrosen 07C03C", density 918 kg / m 3 , MFR15g / 10min Low-density polyethylene resin (L2): "Novatec LDLC720" manufactured by Japan Polyethylene Corporation, density 922 kg / m 3 , MFR9g / 10min Low-density polyethylene resin (L3): Braskem "SBC818", density 918kg / m 3 , Melting point 106℃, MFR 8.1g / 10min
[0133] (2) Formation of a printing layer on a foamed paper material (foamed paper laminate before foaming) The gravure ink prepared above was used to form a printed layer on a foam paper material as described below.
[0134] Example 1 The gravure ink W1 obtained above was diluted with a mixed solvent consisting of methyl ethyl ketone (hereinafter "MEK"): n-propyl acetate (hereinafter "NPAC"): IPA = 40: 40: 20 (mass ratio) so that the viscosity was 16 seconds (25 ° C., Zahn cup No. 3), and printed on a low-density polyethylene resin (L1) foam paper material at a printing speed of 100 m / min using a gravure printing machine with a corrosion resistance of 30 μm to form a printed layer with a thickness of 1.5 μm. The thickness of the printed layer was obtained from a scanning electron microscope (SEM) photograph (magnification 5000) of the cross section of the foam paper laminate. Measurements were taken at five arbitrary points on the printed layer, and the average value of these measurements was taken as the thickness of the printed layer.
[0135] (Examples 2 to 25, Comparative Examples 1 to 3) As shown in Table 4, printing was performed in the same manner as in Example 1, except that each printing ink was used, and a printed layer having a thickness of 1.5 μm was formed. However, in Example 22, overlapping printing was performed, so the printed layer had a thickness of 2.5 μm. In Example 23, low-density polyethylene resin (L2) was used instead of low-density polyethylene resin (L1), and in Example 24, low-density polyethylene resin (L3) was used instead of low-density polyethylene resin (L1).
[0136] (3) Manufacturing example of foamed paper laminate The foamed paper material having a printed layer produced as described above (foamed paper laminate before foaming) was subjected to a heat treatment under the following conditions to foam the low-density polyethylene resin layer (L) to form a foamed layer, thereby producing a foamed paper laminate (laminate after foaming). Standard condition (A): Heated in an oven at 120°C for 6 minutes (Examples 1 to 24, Comparative Examples 1 to 3) Condition (B): Heated in an oven at 122°C for 6 minutes (Example 25)
[0137] <5> Evaluation of foamed paper laminates The foamed paper laminates produced as described above in Examples 1 to 25 and Comparative Examples 1 to 3 were evaluated for various properties according to the methods described below. The results are shown in Table 4.
[0138] <Foaming followability> For each surface of the foamed paper laminates of Examples 1 to 25 and Comparative Examples 1 to 3, the level difference between the ink-printed and non-printed areas after heat treatment (after low Mp film foaming) was touched with a finger, and the degree of depression of the ink-printed area was evaluated according to the following criteria. A higher evaluation value indicates better foaming followability and a flatter printed surface. (Evaluation Criteria) 5: There is almost no noticeable difference in height between the printed and non-printed areas. 4: There is a slight difference in height between the printed and non-printed areas. 3: The difference in height between the printed and non-printed areas is quite noticeable. 2: The gap between the printed and non-printed areas feels quite large. 1: The difference in height between the printed and non-printed areas feels very large.
[0139] <Foaming appearance: blisters> The printed surface of the foamed paper laminate of Examples 1 to 25 and Comparative Examples 1 to 3 was visually observed. The evaluation criteria are as follows. The results shown in Table 4 are the most frequent values obtained by randomly preparing 10 foamed paper laminate samples and observing and evaluating each sample. When there were multiple most frequent values, the value that gave the lowest evaluation was adopted. (Evaluation Criteria) 5: No blisters at all (no blisters visible). 4: A blister with a major axis of less than 5 mm is 100 cm 2 There is one per 3: A blister with a major diameter of less than 5 mm is 100 cm 2 There are two per 2: A blister with a major diameter of less than 5 mm is 100 cm 2 Or, there are 3 to 5 blisters with a major diameter of 5 to 20 mm per 100 cm 2 There is one per 1: A blister with a major diameter of less than 5 mm extends beyond 100 cm 2 There are six blisters per 100 cm. 2 Or, there are two or more blisters with a major diameter of more than 20 mm per 100 cm 2 There is more than one per In addition, if multiple blisters with different major diameters are mixed, the lower rating will be used. 2 If there are two blisters with a long diameter of less than 5 mm and one blister with a long diameter of 5 to 20 mm per unit, the rating will be "2".
[0140] <Foam appearance: cracks> For the foamed paper laminates of Examples 1 to 25 and Comparative Examples 1 to 3, the printed surface of the foamed paper laminate was visually observed in the same manner as in the evaluation of blisters. The evaluation criteria are as follows. The results shown in Table 4 are the most frequent values obtained by randomly preparing 10 foamed paper laminate samples and observing and evaluating each sample. When there are multiple most frequent values, the value that resulted in the lowest evaluation was adopted. (Evaluation Criteria) 5: No cracks at all (no cracks visible). 4: Cracks less than 2mm long are visible for 100cm 2 There is one per 3: Cracks less than 2mm long are visible for 100cm 2 There are 2 to 4 per area. 2: Cracks less than 2mm long are visible for 100cm 2 There are 5 to 10 cracks per 100 cm. 2 There is one per 1: Cracks less than 2mm long are visible for 100cm 2 There are 11 or more cracks per 100 cm. Or, there are 2 to 5 mm long cracks per 100 cm. 2 There are two or more cracks per 100 cm2. Or, there are cracks with a length of more than 5 mm per 100 cm2. 2 There is more than one per In addition, if multiple cracks of different lengths are present, the lower rating will be used. 2 If there is one crack that is 1 mm long and one crack that is 4 mm long, the rating will be "2".
[0141] <Heat resistance> Since it is difficult to directly evaluate the heat resistance of the printed layer during the heat treatment for forming the foamed layer, as an alternative test, the foamed paper laminate (after foaming) was reheated to evaluate the heat resistance. Specifically, first, for the foamed paper laminates of Examples 1 to 25 and Comparative Examples 1 to 3, aluminum foil cut to the same size as the printed layer was superimposed on the surface of the printed layer (coating). Next, using a heat seal tester heated to 140°C, the aluminum foil part was heated to 2 kg / cm 2 The aluminum foil was then peeled off, the area of the ink adhering to the aluminum foil was measured, and the ratio of the ink area to the printed layer was calculated to evaluate the heat resistance. The evaluation criteria were as follows: (Evaluation Criteria) 5: There is absolutely no ink adhesion to the aluminum foil (no ink adhesion can be confirmed). 4: Ink adhesion to the aluminum foil was observed, but it was less than 3%. 3: Ink adhesion to the aluminum foil is 3% or more but less than 10%. 2: Ink adhesion to the aluminum foil is more than 10% but less than 30%. 1: Ink adhesion to the aluminum foil is 30% or more.
[0142] <Ethanol resistance> For the foamed paper laminates of Examples 1 to 25 and Comparative Examples 1 to 3, a Kanakin (JIS L 0803) with 70% ethanol (ethanol:water=70:30) soaked in a friction element was moved back and forth once against the surface of the printed layer (coating) on the low melting point film foamed by heat treatment while applying a load. When the Kanakin was moved back and forth, a load of 200 g was applied using a Gakushin tester (manufactured by Tester Sangyo Co., Ltd.). Thereafter, the coating was visually observed, and the ratio of the area where the coating (ink) had peeled off was calculated based on the total area of the coating before the test, to evaluate the ethanol resistance. The evaluation criteria are as follows. (Evaluation Criteria) 5: Less than 30% of the ink has peeled off. 4: Ink peeling is more than 30% but less than 40%. 3: Ink peeling is more than 40% but less than 60%. 2: Ink peeling is more than 60% but less than 70%. 1: More than 70% of the ink has peeled off.
[0143] Although not shown in Table 4, other properties, such as the thickness of the foam layer and the number of foam cells of the foamed paper laminate, were measured according to the method described below. As a result, for all of the foamed paper laminates except for Comparative Example 3, the thickness of the foam layer was 500 μm or more, and the number of foam cells was 1250 / 1 cm. 2 From the above, it was confirmed that sufficient heat insulation for practical use was obtained. On the other hand, in the foamed paper laminate of Comparative Example 3, although the thickness of the foamed layer exceeded 500 μm, the number of foamed cells was 1000 pieces / 1 cm. 2 Therefore, sufficient heat insulation for practical use could not be obtained.
[0144] (Number of foam cells) The printed layer of the foamed paper laminate was removed with methyl ethyl ketone (MEK) to expose the surface of the foamed thermoplastic resin layer (foamed layer). The surface of the foamed layer was then observed (magnification: 25x) using an optical microscope (Nikon, AZ100M) to determine the number of closed cells present within a range partitioned by a certain length in the vertical and horizontal (XY) directions, and then counted by 1cm. 2The number of closed cells per unit area was calculated. Observations were made at five randomly selected locations, and the average of these was taken as the number of foam cells.
[0145] (Thickness of foam layer) The thickness of the foam layer was determined by observing the cross section of the foamed paper laminate with an optical microscope and measuring the height from the top surface of the paper base material to the bottom surface of the printed layer. The thickness before foaming corresponds to the thickness of the foam-layer-forming layer. Therefore, the thickness was determined by measuring the thickness of the low-density polyethylene resin formed as the foam-layer-forming layer.
[0146] [Table 4]
[0147] From the results shown in Table 4, it can be seen that, according to the embodiment (example) of the present invention, by using a urethane resin containing a structural unit derived from castor oil polyol as a binder resin, excellent heat resistance, foaming followability, foaming appearance, and ethanol resistance can be obtained. In particular, it can be seen that heat resistance can be easily improved when castor oil polyol and polyester polyol are used in combination as the polyol component. In contrast, in the comparative example using a urethane resin not containing a structural unit derived from castor oil polyol, the desired properties could not be obtained, and in particular, the heat resistance and alcohol resistance were significantly reduced. From the above, it can be seen that the present invention provides a foamed paper laminate that has a printed layer containing a biomass resin, has excellent heat resistance, foaming followability, foamed appearance, and ethanol resistance, and can be suitably used as a component of a foamed paper container.
[0148] (Explanation of symbols) 10 Foamed paper laminate (container body member) 10A Foam paper container 10a Outer wall surface of container 10b Inner wall surface of container 12 Bottom plate member 12 20 High Mp resin film (thermoplastic resin layer (A)) 30 Paper base material 40 Low Mp resin film after foaming (foamed thermoplastic resin layer (B), foamed layer (B)) 50 printing layers 50a Base layer 50b Printing pattern
Claims
1. A foamed paper laminate comprising a base paper, a foamed paper consisting of a thermoplastic resin layer (A) provided on one side of the base paper, and a foamed thermoplastic resin layer (B) provided on the other side of the base paper, and a printed layer provided on the foamed thermoplastic resin layer (B), The printing layer contains at least a binder resin, The binder resin contains a urethane resin having a structural unit derived from castor oil polyol, The foamed paper laminate, wherein the number of foamed cells per unit surface area of the foamed thermoplastic resin layer (B) is 1000 cells / 1 cm 2 or more.
2. The foamed paper laminate according to claim 1, wherein the urethane resin further has a structural unit derived from a polyester polyol which is a condensate of a dibasic acid and a diol, and the mass ratio (a1) / (a2) of the structural unit (a1) derived from the castor oil polyol to the structural unit (a2) derived from the polyester polyol is 75 / 25 to 10 / 90.
3. 3. The foamed paper laminate according to claim 1, wherein the content of structural units derived from polyether polyol is 8% by mass or less based on the total mass of the urethane resin.
4. The foamed paper laminate according to any one of claims 1 to 3, wherein the castor oil polyol has a weight average molecular weight of 1,000 to 5,000.
5. The foamed paper laminate according to any one of claims 1 to 4, wherein the binder resin further contains a vinyl chloride / vinyl acetate copolymer, and the content of the vinyl chloride / vinyl acetate copolymer is 5 mass% or more and 50 mass% or less based on the total mass of the binder resin.
6. The foamed paper laminate according to any one of claims 1 to 5, wherein the binder resin has an elongation rate of 400% to 3,000%.
Citation Information
Patent Citations
Laminate and method for manufacturing laminate
JP2014004799A
Alcohol-based printing ink composition
JP2014005414A
Lid material and packaging container using the same
JP2015231870A
Aqueous flexo ink for foam cup, and foam cup
JP2018058955A
Gravure ink, and printed matter and laminate comprising the same
JP2018109131A